2006
DOI: 10.1007/s10900-006-9018-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Sources Of Support For Diabetes Self-Care In Urban And Rural Underserved Communities

Abstract: The ability of adults with diabetes to manage their illness properly and prevent complications is, in part, a function of support provided by the people and institutions surrounding them. Using data from over 200 adults with diabetes in two medically underserved communities--one urban and one rural--this study examines the self-care specific support provided by four key sources: family and friends, community organizations, one's neighbors and neighborhood, and resources in the wider community. More specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
53
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 17 publications
4
53
1
1
Order By: Relevance
“…Although aspects of community disadvantage have been associated with the incidence of diabetes [61], neither the present study nor a recent study with urban African Americans [60] detected direct associations with HbA 1c . Detection of direct effects, if they exist, may be hampered by the more distal influence of neighborhood conditions and a number of intermediary, confounding variables such as access to health care [30] and access to and support for adherence to dietary and exercise recommendations [62]. Consistent with studies focused on community samples and persons with chronic disease, educational attainment, community disadvantage, and financial distress were significant predictors of depressive symptoms.…”
Section: Discussionmentioning
confidence: 87%
“…Although aspects of community disadvantage have been associated with the incidence of diabetes [61], neither the present study nor a recent study with urban African Americans [60] detected direct associations with HbA 1c . Detection of direct effects, if they exist, may be hampered by the more distal influence of neighborhood conditions and a number of intermediary, confounding variables such as access to health care [30] and access to and support for adherence to dietary and exercise recommendations [62]. Consistent with studies focused on community samples and persons with chronic disease, educational attainment, community disadvantage, and financial distress were significant predictors of depressive symptoms.…”
Section: Discussionmentioning
confidence: 87%
“…These findings are consistent with studies that demonstrate the importance of social networks for patients with diabetes, particularly for those in underserved communities. 32,33 It may be useful for clinicians to assess social support at the time of diagnosis. This can be achieved using a tool such as the Social Network Map 34 that prompts patients to describe and discuss the quality and scope of their social support system.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several studies on diabetes have found that support from family and friends can motivate people with type 2 diabetes to engage in glucose monitoring, healthier eating habits and increased physical activity. [5][6][7][8][9][10][11][12] In addition, studies have demonstrated that higher levels of family and friends support may be associated with better diabetes management. 11,13 Although most diabetes research has assumed that social support is constructive, there are considerable challenges in the research about social support from family and friends and its influence on self-management in type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%